Evidence for Correlation between Novel Autoantibody against Phospholipid Named Neoself Anti-β2-GPI/HLA-DR Antibody and Complement Consumption in Infertile Patients - Hirotaka Matsumi (Hindawi Limited, 2023)
Impaired implantation is one of the causes of infertility. It occurs under vital inflammatory status due to immune hyperactivation. In the innate immune system, the inflammatory response to pathogenic stimuli is initiated by complement activation. Minimal vasculitis associated with complement consumption in infertile patients may be an underlying mechanism for impaired implantation. Antiphospholipid antibodies regulate the inflammatory response. Recently, a novel autoantibody (neoself antibody) against a complex of β2-GPI and HLA class II molecules (β2-GPI/HLA-DR) has been reported to be an independent autoantibody associated with aPLs. This study investigated the relationship between neoself antibodies and complement consumption in infertile patients with impaired implantation. It was found that decreased C4 levels were strongly related to the increased neoself antibody titers in the serum among those patients whose antibody titers were not as high. On the contrary, serum levels of CH50 and CRP are not correlated with them. These results suggest that neoself antibodies might indicate low-grade inflammation, which causes endometrial vasculitis in impaired implantation of infertile patients.